Decision Difficulty in the Age of Consumer Empowerment - Broniarczyk, Susan M.; Griffin, Jill G. (Journal of Consumer Psychology, 2014)
AbstractIn this review, we examine the impact of two key factors of consumer empowerment–choice freedom and expansion of information‐‐on the choice difficulty consumers experience in today's decision environment. We posit that though these two consumer empowerment factors offer numerous potential benefits, they also can magnify such sources of decision difficulty as task complexity, tradeoff difficulty, and preference uncertainty. Next we review several key moderators, including consumer knowledge, mental representation, and maximization tendencies as well as information type and organization, that can exacerbate or mitigate the effect of these consumer empowerment factors on decision difficultly outcomes. Lastly, we examine the effectiveness of decision aids in assisting consumers navigate the complexity of today's decision environment, and we identify areas for future investigation.